Relation of postoperative serum S100A12 levels to delirium and cognitive dysfunction occurring after hip fracture surgery in elderly patients. Issue 1 (11th December 2018) - Li, Qing‐Hua; Yu, Liang; Yu, Zheng‐Wei; Fan, Xiao‐Liang; Yao, Wang‐Xiang; Ji, Cheng; Deng, Fang; Luo, Xian‐Zhe; Sun, Jian‐Liang
Abstract: Objective: Brain injury is implicated in pathogenesis of postoperative delirium (POD) and cognitive dysfunction (POCD). S100A12 is involved in inflammatory process and is recently known as a biomarker for brain injury. Herein, we clarified whether serum S100A12 levels are related to POD and POCD after hip fracture surgery in elderly patients. Materials and Methods: In this prospective, observational study, we gauged S100A12 levels in preoperative and postoperative serum from 186 patients and serum from 186 controls. Patients were categorized according to the presence of POD and POCD. Results: Postoperative, but not preoperative serum S100A12 levels were significantly higher in patients than in controls. There was a positive and independent correlation between postoperative C‐reactive protein and S100A12 levels ( t  = 8.797, p  < 0.001). Postoperative S10012 levels and age were independently associated with the risk of developing POD (S100A12 levels: odds ratio [OR] = 1.166, 95% confidence interval [CI] = 1.045–2.087, p  = 0.001; age: OR = 1.243, 95% CI = 1.073–1.419, p  = 0.012) and POCD (S100A12: OR = 1.157, 95% CI = 1.030–1.986, p  = 0.003; age: OR = 1.228, 95% CI = 1.054–1.387, p  = 0.014). In terms of area under receiver operating characteristic curve, postoperative S100A12 levels had a higher predictive ability than age and their combination dramatically exceeded that of each one alone. Conclusions: Postoperative elevated serum S100A12 levels have a strong relation to inflammation and are associated independently with the development of POD and POCD, substantializing serum S100A12 as a potential biomarker for predicting POD and POCD in elderly patients undergoing hip fracture surgery. Abstract : Elevated S100A12 levels in serum after hip fracture surgery in elderly patients. Independent relation of postoperative serum S100A12 to delirium and cognitive dysfunction after hip fracture surgery. High discriminatory ability of postoperative serum S100A12 for delirium and cognitive dysfunction after hip fracture surgery.